MON-116 Metabolic Parameters in Cancer Patients with and Without Diabetes Mellitus - Karlin, Nina (J Endocr Soc, 2020)
Background: We have previously examined the link between diabetes mellitus (DM) and malignancy with respect to mortality, but little is known about how the cancer affects glycemic control. Therefore, the aim of this study was to evaluate metabolic parameters in patients with cancer with and without DM. Methods: We selected 1404 patients with newly diagnosed prostate, breast, lung, colorectal, and pancreatic cancer from the institutional cancer registry from 2010–2015. Records were selected and matched 2:1 cancer without DM (n=936) and cancer and concurrent DM patients (n=468). Patients were matched by year of diagnosis, age, gender, and cancer type. Metabolic parameters during the year after cancer diagnosis were examined using linear mixed models with fixed effects for time, cancer type, DM status and individual-specific random effect allowing each patient to have a different intercept. Results: Prostate cancer accounted for the majority of cases (n=199), followed by lung cancer (n=91), breast cancer (n=71), colorectal cancer (n=54), and pancreas cancer (n=53). Mean overall hemoglobin A1c (HbA1c) was 6.9 (1.2)%. Pancreas cancer patients had higher HbA1c overall (p=0.02). There was no change in HbA1c one year post cancer diagnosis (p=0.28). Mean glucose in non-DM was 108(18) mg/dL and 146 (45) mg/dL in DM pts. Lung and pancreas cancer patients had higher glucose values overall (p<0.001). Time (p<0.001), DM (p<0.001) and time * DM (p=0.02) were significant in a mixed model. A decrease in glucose over the year was observed in DM patients across all cancer types. Conclusions: A diagnosis of malignancy does not worsen glycemic control within the first year of cancer diagnosis. This should be reassuring to endocrinologists and oncologists who treat patients with DM and cancer. Longer term studies, and analysis in larger and more diverse patients groups are needed.